1998
DOI: 10.1098/rspb.1998.0537
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamic interference among childhood diseases

Abstract: Epidemiologists usually study the interaction between a host population and one parasitic infection. However, di¡erent parasite species e¡ectively compete, in an ecological sense, for the same ¢nite group of susceptible hosts, so there may be an indirect e¡ect on the population dynamics of one disease due to epidemics of another. In human populations, recovery from any serious infection is normally preceded by a period of convalescense, during which infected individuals stay at home and are e¡ectively shielded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 34 publications
5
74
0
1
Order By: Relevance
“…Seasonal pathogens might therefore function as competing disease risks among each other while remaining independent of many other risk factors. Competitive interactions among seasonal pathogens can have substantial disease dynamic consequences (Rohani et al 1998(Rohani et al , 2003. We hypothesize that they may also modify disease impacts on the host population.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal pathogens might therefore function as competing disease risks among each other while remaining independent of many other risk factors. Competitive interactions among seasonal pathogens can have substantial disease dynamic consequences (Rohani et al 1998(Rohani et al , 2003. We hypothesize that they may also modify disease impacts on the host population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that epidemiological interference can potentially have important consequences for the design of effective immunization schemes (53). Currently, there are no vaccines for RSV or HPIV, although research is underway (18,54,55).…”
Section: Discussionmentioning
confidence: 99%
“…This interaction between strains arises by competition for susceptible hosts and the temporary removal of individuals after infection because of quarantining or convalescence (43,44,53). In respiratory viral infections, such as RSV, child patients are often sent home or to the hospital until they are recovered or cured.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of an impact of E. maimaiga on LdNPV density dependence is surprising given that the short disease cycle of E. maimaiga allows this fungal pathogen to ''beat'' LdNPV when hosts are simultaneously infected. Additionally, there is good evidence from human disease systems that the presence of one fatal pathogen can interfere with the dynamics of a cooccurring disease via ''ecological interference'' in which susceptibles are removed by a competing pathogen, thereby altering the conditions for mass action (Rohani et al 1998). Malakar et al (1999a) suggested that one reason for the lack of a direct effect of E. maimaiga on LdNPV seasonal mortality may be that E. maimaiga mortality is typically highest in late instars, and by that time, the course of any LdNPV epizootic may have already been determined.…”
Section: Discussionmentioning
confidence: 99%